Seasonal distribution of nanoflagellates and bacterioplankton and relationship with environmental factors in a brazilian semi-arid reservoir - doi: 10.4025/actascibiolsci.v34i4.10832 (Acta Scientiarum. Biological Sciences, 2012)
The semi-arid region of Rio Grande do Norte State, in northeast Brazil exhibits specific physical-climatic aspects: the climate is very hot, with mean annual rainfall of 550 mm, characterized by periodic drought and uneven distribution of rains. Due to these features, is important to study and preserve its water bodies. The purpose of this paper was to characterize and investigate bacterioplankton and heterotrophic nanoflagellates, and their seasonal variations in a reservoir located in the semi-arid region of Rio Grande do Norte State, in 2008. To this aim, four samplings were carried out in the rainy season and three in the dry season to determine the biotic and abiotic variables. Bacterial densities in the reservoirs ranged from 8.98 x 106 to 1.62 x 107 bac mL-1, while total biomass varied between 207 and 262 Î¼gCL-1. The nanoflagellates showed a variation between 1,777 and 8,229 org mL-1 in density, and between 3.0 and 9.6 Î¼gCL-1 in biomass. Statistical analyses presented non-standard results for both biological and physical-chemical variables throughout the study year, revealing the complexity of the reservoir with respect to the mechanisms controlling the microbial populations analyzed.